Global disability-adjusted life years and deaths attributable to child and maternal malnutrition from 1990 to 2019 - Liu, Rong; Pi, Lucheng; Leng, Fangqun; Shen, Qing (Frontiers in Public Health, 2024)
Background: Child and maternal malnutrition (CMM) caused heavy disability-adjusted life years (DALY) and deaths globally. It is crucial to understand the global burden associated with CMM in order to prioritize prevention and control efforts. We performed a comprehensive analysis of the global DALY and deaths attributable to CMM from 1990 to 2019 in this study. Methods: The age-standardized CMM related burden including DALY and death from 1990 to 2019 were accessed from the Global Burden of Disease study 2019 (GDB 2019). The changing trend were described by average annual percentage change (AAPC). The relationship between sociodemographic factors and burden attributable to CMM were explored by generalized linear model (GLM). Results: Globally, in 2019, the age-standardized DALY and death rates of CMM were 4,425.24/100,000 (95% UI: 3,789.81/100,000–5,249.55/100,000) and 44.72/100,000 (95% UI: 37.83/100,000–53.47/100,000), respectively. The age-standardized DALY rate (AAPC = -2.92%, 95% CI: -2.97% to -2.87%) and death rates (AAPC = -3.19%, 95% CI: -3.27% to -3.12%) presented significantly declining trends during past 30 years. However, CMM still caused heavy burden in age group of < 28 days, Sub-Saharan Africa and low SDI regions. And, low birth weight and short gestation has identified as the primary risk factors globally. The GLM indicated that the highly per capita gross domestic product, per capita current health expenditure, physicians per 1,000 people were contributed to reduce the burden attributable to CMM. Conclusion: Although global burden attributable to CMM has significantly declined, it still caused severe health burden annually. To strengthen interventions and address resources allocation in the vulnerable population and regions is necessary.